Epidemiology of idiopathic inflammatory myopathies in africa: a contemporary systematic review - (:unkn) unknown (My University, 2022)
BACKGROUND: The epidemiology of idiopathic inflammatory myopathies (IIMs) has been extensively studied in America, Europe, and Asia, but remains unclear in Africa.OBJECTIVE: The aim of this review was to summarize available data on the epidemiology of IIMs in Africa.METHODS: We searched MEDLINE, EMBASE, and African Journals Online for studies published up to December 30, 2020, and reporting epidemiological data on IIMs in Africa. Data were combined through narrative synthesis. The review protocol was registered with PROSPERO, CRD42020186781.RESULTS: We included 39 studies reporting 683 cases (71.7% adults) of IIMs. Incidence rates of ~7.5/1,000,000 person-years and 1.2/1,000,000 person-years were estimated for dermatomyositis (DM), whereas polymyositis (PM) had an incidence rate of 8.8/1,000,000 person-years. Prevalence estimates of 11.49/100,000 and 11/100,000 (95% confidence interval, 0-32) were provided for IIMs and the PM subtype, respectively. Mean age at diagnosis ranged from 7.9 to 57.2 years, and 50% to 100% of the patients were females. Main subtypes of adult-onset IIMs were DM (21%-93%) and PM (12%-79%), whereas the commonest juvenile subtype was juvenile DM (5.8%-9%). Skeletal muscle involvement (56%-100%) was the main disease feature, and esophagus was the most commonly affected internal organ (6%-65.2%). Anti-Jo1/histidyl tRNA synthetase (7%-100%) and anti-Mi2 (17%-45%) antibodies were the most frequent myositis specific antibodies. Early mortality was high (7.8%-45%), and main death causes were infections, cancers and organ damage in respiratory and cardiovascular domains.CONCLUSIONS: Apart from a potential younger age at onset of adult IIMs in Africa, current sparse data mostly suggest a similar epidemiology between Africa and other regions. Further high-quality studies are required to validate these findings.
Keywords: African Research